Az ún. első Basch-per : A politikai elkötelezettség jogi büntetése - Norbert, Spanneberger (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
At the beginning of the 1930s, the Ethnic German Movement (‘Volksdeutsche Bewegung’) in Hungary became radicalised. The reasons for that were on the one hand the lacking organisation of the nationalities movement and on the other hand the exerted pressure on members of the Volksdeutsche Movement through the Gömbös government. The most significant incident was the first Basch trial in 1934, in which Franz Basch, an active member of the movement and later Volksgruppenführer of the Germans in Hungary on the initiative of Berlin authorities, was put on trial for a statement on the Magyarization of names. The charge in the (secret) trial and later reason for conviction was the alleged ‘insult to the Hungarian nation’. Overall, the trial and its context (including Basch’s pardon 1937 and his acquittal 1941) show the high degree of politicisation of the minority question in German-Hungarian relations during the second half of the Horthy era.